PENGEMBANGAN MATERI PAI BERWAWASAN MULTIKULTURAL DALAM UPAYA MENANAMKAN NILAI KERAGAMAN BAGI SISWA - Muhiddinur Kamal; Junaidi Junaidi (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
THE DEVELOPMENT OF ISLAMIC EDUCATION ON MULTICUKTURAL  IN DEVELOPING THE DIVERSITY VALUE  Comprehensive understanding of multiculturalism by all components of the nation of children living in Indonesia is very important in building the life of nation and state. Therefore the application of multicultural education in schools becomes a demand considering the conflicts. One attempt to provide that understanding is to teach materials that are multicultural in school. This research is focused on multicultural PAI teaching materials. This study aims to develop PAI materials with multicultural insight as an effort to instill diversity values in SMKN 1 Ampek Nagari Agam district. This research includes development research. the development model used adapted from the McKenny Model. Research has resulted in PAI learning tools that are multicultural in the form of, RPP, and teaching materials that are valid, practical and effective.